Crop insurance: Ethiopia - Tadesse, Mulugeta; Tekle, W.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
Developed in collaboration with a private company that offers agro-advisory services to farmers, the Area Yield Index Insurance (AYII) Tool reduces reliance on crop-cutting for insurance payouts.